Start by distributing -6 to x and -7 on the left side, and distributing -2 to 4 and 3x on the right side. This will cancel out our parentheses.
Now get x to one side of the equation. Add 6x to both sides.
x ends up cancelling out on both sides. There is no solution for x in this equation, because you end up with -42=-8, which is not a true statement.
-6(x-7) = -2(4+3x) simplify on both sides
-6x + 42 = -8 - 6x
-6x + 42 = -6x - 8
There is no solution to this because adding 42 to -6x can't possibly equal the same thing as subtracting 8 from -6x